The Impact of Key Sectors on Economic Growth: A Cross-Country Analysis - Farawi Ghannili; Miftahul Choiri (Jurnal Ekonomi Pembangunan)
Economic growth is a multifaceted phenomenon driven by various sectoral contributions. This study investigates the impact of exports, imports, including key economic sectors, such as manufacturing, agriculture, services, and construction, on economic growth in developing and developed countries. It uses time series data from Q2-2011 to Q2-2023 and seven countries, i.e. Indonesia, China, India, France, Germany, the United Kingdom, and the United States. It applies panel data regression with the fixed effect-least square dummy variable method. The findings reveal that exports, manufacturing, agriculture, and services have positive and statistically significant effects on economic growth. In contrast, imports and construction show negative impacts. These findings underscore the importance of fostering export-oriented industries, promoting technological innovation in manufacturing, supporting sustainable agricultural practices, and developing a vibrant service sector. In turn, policymakers should address the potential negative consequences of excessive import dependence and strive to improve the efficiency and productivity of the construction sector. These findings provide implications for policymakers to formulate and implement effective economic growth strategies that prioritize sustainable development and inclusive growth.